Same-Sex and Different-Sex Interracial Couples: The Importance of Demographic and Religious Context - Jones, Nicole E. (Race and social problems, 2021)
How does demographic and religious context relate to interracial relationships among same-sex and different-sex couples? Using couple data from the 2012 to 2014 American Community Surveys matched to aggregate data from the 2010 Census and 2010 Religious Congregations and Membership Study, we test how heterogamy patterns for same-sex and different-sex couples vary by the demographic and religious makeup of cities, using multinomial logistic regressions to compare interracial and same-race couples. We find that same-sex couples are more likely to be in a White/Black interracial pairing than different-sex couples. White partners are more likely to be in an interracial relationship if they are in a city with a large minority group population. In addition, context is differently associated with interracial unions for same-sex and different-sex couples, varying for each racial combination.